The Effects of Passive Cigarette Smoke Exposure on the Survival of the Reverse Sural Fasciocutaneous Flap - Sadagatullah, Abdul Nawfar; Halim, Ahmad Sukari; Bathusha, Mohd Shakir; Ramachandran, Anantha Kumar (Journal of Hand and Microsurgery, 2017)
Background The possibility of a person who had undergone surgery to be exposed to the ill effects of cigarette smoke is high, more so if the person lives with a smoker. With increasing popularity of reverse sural fasciocutaneous flaps, a surgeon may have to manage a person who lives with a smoker or is exposed to cigarette smoke. A clear understanding of the effects of exposure to cigarette smoke on reverse sural fasciocutaneous flaps is necessary. This study was performed to establish a clearer understanding of the effects of smoking on reverse sural fasciocutaneous flaps and evidence for preoperative patient counseling about smoking and smoke exposure.Objective The study investigated effects of exposure to cigarette smoke on the survival of the reverse sural fasciocutaneous flap.Methods This was an experimental observational study conducted at the Laboratory for Animal Research Unit in the Health Campus of Universiti Sains Malaysia. Twelve adult White New Zealand rabbits (Oryctolagus cuniculus) were divided into two groups of six. All 12 rabbits had a 2.5- × 2.5-cm reverse sural fasciocutaneous flap raised on both its hind limbs. The group exposed to cigarette smoke underwent 4 weeks of smoke exposure for 2 hours daily prior to surgery. This was then continued until analysis of the results.The control group had no intervention. All flaps were analyzed on the seventh postoperative day, after tracing on transparent plastic sheets with the necrotic area marked followed by 2D planimetry done on a grid paper. The flaps were assessed on the total flap area and survival area percentage. It was recorded as mean ± SD. The presence or absence of infection and hematoma was also noted.Results Twelve flaps were analyzed in each group. Total mean flap area and survival area percentage of the control group were 120.33 ± 31.03 mm2 and 80.12 ± 15.75%, respectively, whereas in the cigarette smoke–exposed group, it was 121.83 ± 17.93 mm2 and 62.04 ± 34.01%, respectively. The control group had two infections and one hematoma, and the smoking-exposed group had six infections and nine hematomas. The comparison between the groups was made in terms of total flap area, survival percentage, presence of infection, and hematoma for which the p values were 0.886, 0.115, 0.083, and 0.003, respectively. The differences between right and left hind limbs were also analyzed (p = 0.414).Conclusion There was no statistical difference in the results from the right and left hind limbs. There was no statistical difference in the survival of reverse sural fasciocutaneous flap between the control and smoking-exposed groups.
Keywords: passive cigarette smoke exposure; fasciocutaneous skin flap; rabbit experimentation